Pengaruh Lama Ensilase dan Aras Bioaktivator EM4 terhadap Kualitas Fisik dan Kandungan HCN Silase Kulit Ubi Kayu (Manihot utilissima Pohl) - Raguati Raguati; Darlis Darlis; Afzalani Afzalani; Zulia Ningsi; Fachroerrozi Hoesni; Endri Musnandar (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study was aims to determine the effect of ensilage duration and EM4 bioactivator arasto produce good physical quality and the lowest HCN content in cassava peel silage. The design used was a completely randomized design with a factorial pattern (4×3) with 3 replications. The first factor (A) ensilage duration (A0 = no ensilage, A1 = 7 days, A2 = 14 days and A3 = 21 days) and the second factor (B) EM4 levels (B0 = 0%, B1 = 2% and B2 = 4 %). The observed variables included physical quality in the form of color, texture, odor, pH, percentage of shrinkage, and HCN content of cassava peel silage. The data obtained were analyzed with SAS version 9.1 for parametric data.. Meanwhile, non-parametric data was processed using the Kruskal-Wallis test, if it had a significant effect, it was continued with the Wilcoxon test. The results showed that the ensilage duration had a significant effect (P<0.05) on color, odor, texture, pH, percentage of shrinkage and HCN content. The EM4 arashad a significant effect (P<0.05) on the color, odor, texture and HCN content but no significant effect (P>0.05) on the pH and the percentage of shrinkage. The interaction between ensilage time and EM4 arashad a significant effect (P<0.05) on texture, pH and HCN content, however there are not significant effect (P>0.05) on color, odor and percentage of shrinkage. The study was concluded that ensilage process up to 21 days and inclusion EM4 at 4% arasresulted in good physical quality and lowest HCN content of cassava peel silage.